PRIMARY CUTANEOUS AGGRESSIVE EPIDERMOTROPISM CD8+ CYTOTOXIC T-CELL LYMPHOMA: SEBUAH KASUS SULIT (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2023)
Introduction: Primary cutaneous aggressive epidermotropism CD8+ cytotoxic t-cell lymphoma (PCAE-CD8+ CTCL) is an aggressive variant of cutaneous T-cell lymphoma which has poor prognosis. Because of its rarity, its relatively variable clinical dan histopathological presentation, and no diagnostic criteria for PCAE-CD8+ CTCL, establishing diagnosis can be challenging. Case: A case of PCAE-CD8+ CTCL in a 67-year-old man whose early histopathological features resembling parapsoriasis was reported. Physical examination showed multiple lesions in form of erythematous plaques with ulcers and crusts in almost part of the body. Histopathological features showed epidermotropism and infiltrates of atypical also pleomorphic lymphocytes. Immunohistochemistry result was positive for CD8, CD4, Granzyme, CD3, and Ki-67 supported PCAE-CD8+ CTCL. Discussion: Clinical manifestation of PCAE-CD8+ CTCL varies among patients. Histopathological and immunohistochemistry examination are needed to establish diagnosis. Conclusion: The understanding of clinical manifestation of PCAE-CD8+ CTCL is needed. Because of its poor prognosis and high proliferative activity, early diagnosis may be helpful in improving the likelihood of patient survival.